1997
DOI: 10.1177/112067219700700108
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dosage Mitomycin C as an Adjunct to Trabeculectomy. A Prospective Controlled Study

Abstract: Mitomycin C is a useful adjunct to glaucoma surgery. Adverse effects at the dosage used are mainly due to hypotony and are preventable with two-layer suture. Low-dose mitomycin C may be useful in standard primary trabeculectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…The use of intraoperative-MMC reduces the risk of surgical failure both in eyes at high risk of surgical failure 389,390 and in eyes that have not undergone previous surgery. [390][391][392][393] Some studies have demonstrated a benefit of intraoperative 5-fluorouracil 394,395 and others have not. 396 Intraoperative 5-fluorouracil and MMC were found to be equally safe and effective adjuncts to primary trabeculectomy in a multicenter randomized clinical trial.…”
Section: Trabeculectomymentioning
confidence: 99%
“…The use of intraoperative-MMC reduces the risk of surgical failure both in eyes at high risk of surgical failure 389,390 and in eyes that have not undergone previous surgery. [390][391][392][393] Some studies have demonstrated a benefit of intraoperative 5-fluorouracil 394,395 and others have not. 396 Intraoperative 5-fluorouracil and MMC were found to be equally safe and effective adjuncts to primary trabeculectomy in a multicenter randomized clinical trial.…”
Section: Trabeculectomymentioning
confidence: 99%
“…In routine clinical practice antifibrotic agents such as mitomycin C (MMC) or 5-fluorouracil are used during or after surgery to prevent postoperative scarring [3,4,5,6]. Though MMC and 5-fluorouracil cause widespread cell death and apoptosis, the risk profile seems moderate.…”
Section: Introductionmentioning
confidence: 99%
“…1 Adjunctive anti-fibrotic agents such as 5-fluorourail or mitomycin C (MMC) have a potent inhibitory effect on postoperative scarring and a positive effect on surgical success rates. 2,3 Although the risk profile of additional use of MMC in trabeculectomy appears low, some side effects such as cataract formation, avascular filtering blebs, thinning of the conjunctiva, subsequent blebitis, and endophthalmitis have been described. [3][4][5][6] Recently, tissue-engineered biodegradable implants have been created as an alternative augmentation in trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%